The impact of cultural healthcare practices on Children's health in the United Arab Emirates: a qualitative study of traditional remedies and implications - Nabeel Al-Yateem; Nabeel Al-Yateem; Amal Muneer Abobakr Lajam; Mariam Mohamad Gouda Othman; Maryam Ahmed Ali Ahmed; Shayma Ibrahim; Aram Halimi; Aram Halimi; Fatma Refaat Ahmad; Fatma Refaat Ahmad; Muhammad Arsyad Subu; Muhammad Arsyad Subu; et al. (Frontiers Media S.A., 2023)
AimThis qualitative study investigates the impact of cultural practices on children's health in the United Arab Emirates (UAE) by examining the use of traditional remedies and home treatments by mothers.MethodsTwenty-five participants, all mothers who had employed traditional treatments or home remedies for their children during periods of illness, were included in the study. The participants represented a diverse range of educational backgrounds, from school diploma holders to university degree graduates, with ages spanning from 20 to 50 years. Hailing from different Arabic countries and cultural subgroups, the majority of participating mothers were from the UAE.ResultsThrough in-depth interviews, three major themes emerged from the participants' experiences. Firstly, a strong connection between culture, religion, and healthcare practices was evident. Many mothers opted for cultural remedies as their first line of defense against illnesses due to the practices' strong foundations in their cultural heritage. Herbal remedies, Quranic healing, and other traditional methods were perceived to be both effective and spiritually comforting, reinforcing participants' sense of cultural identity. Secondly, participants highlighted unintended consequences of relying solely on traditional treatments. Some instances were reported where the use of ineffective remedies resulted in delays in seeking appropriate medical care for their children, potentially compromising their health. Additionally, certain misconceptions regarding the safety and efficacy of traditional remedies were identified, emphasizing the need for evidence-based healthcare education.ConclusionThis qualitative study sheds light on the intricate interplay between culture, traditional remedies, and children's health in the UAE. The incorporation of diverse participants from various Arabic countries and cultural subgroups enriches the study's applicability to broader Arabic cultures. By recognizing the significance of cultural healthcare practices and striking a balance with evidence-based care, healthcare providers can create a more inclusive and effective healthcare environment for children in the UAE. Future research should explore diverse samples and develop targeted interventions to further advance cultural awareness and understanding in healthcare practices.